La cultura tributaria en estudiantes del sexto ciclo de la carrera profesional de contabilidad del Instituto Superior Tecnológico Pedro A. Del Águila Hidalgo, 2021 - Guevara Garcia, Max Valery (2022)
The present research work entitled "Tax Culture in Students of the Sixth Cycle of the Professional Accounting Career of the "Instituto Superior Tecnológico Pedro A. del Águila Hidalgo, 2021" was carried out with the objective of determining what is the level of tax culture that they have. the students of the sixth cycle of the Accounting professional career of the Instituto Superior Tecnológico "Pedro A del Águila Hidalgo" in 2021, for which the type of descriptive research was used and the design of the research was Non-Experimental, it was taken into account as study population 108 students duly enrolled in the sixth semester to whom a survey was applied with the data collection instrument called a questionnaire; the work concluded that the students have a high level of Tax Culture.